Marketers and Avertisers and the Concept Called “Aggressive Marketing Tendency (ATM)” - Bethel Chidiebere Uzoagba; Micheal A. Nza-Ayang; Olimma Benedette Ngozi (MultiTech Publisher, 2024)
In recent times, advertisers and marketers have realised that constant exposure to outdoor advertisement increases the tendency of brand familiarity as a result, propels patronage. Okoro (1998:77) supports this when he said that outdoor advertising makes product highly visible to the consumers, thereby enhancing recall-readiness of brand names. This is because the advert message is viewed so many times a day by same people. As a result helps to fix the brand name on the consumers’ mind